Asset Life Sukuk to Fund Utility Companies - Biancone, Paolo Pietro; Shakhatreh, Mohammad Ziad (European Journal of Islamic Finance, 2017)
In response to a growth in the world population, there has been a growth in demand for utilities; In fact government and utility companies are increasingly looking to alternative sources of finance to meet these growing demands. This paper will provide evidence that Sukuk is one of the vehicles for funding utilities which can fill the gaps between available sources and customer needs. A qualitative research approach has been used to examine the main characteristics of investment in the utility sector and compare them with Sukuk features. The paper explains the process of choosing and developing the Sukuk structure to fit the main originator objectives. The paper concludes that Sukuk can meet utility companies’ needs, and the paper suggesting that utility company can use the Sukuk structure with no redemption value.